2011
DOI: 10.1002/eji.201141956
|View full text |Cite
|
Sign up to set email alerts
|

Natural variations at position 93 of the invariant Vα24‐Jα18 α chain of human iNKT‐cell TCRs strongly impact on CD1d binding

Abstract: Human invariant natural killer T (NKT) cell TCRs bind to CD1d via an ''invariant'' Va24-Ja18 chain (iNKTa) paired to semi-invariant Vb11 chains (iNKTb). Single-amino acid variations at position 93 (p93) of iNKTa, immediately upstream of the ''invariant'' CDR3a region, have been reported in a substantial proportion of human iNKT-cell clones (4-30%). Although p93, a serine in most human iNKT-cell TCRs, makes no contact with CD1d, it could affect CD1d binding by altering the conformation of the crucial CDR3a loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
2
10
1
Order By: Relevance
“…Moreover, these TCR-α variations strongly influenced the affinity of human iNKT TCRs for various antigenCD1d complexes, irrespective of the TCR-β chain with which they were paired (39). However, in contrast with our results where variations were most common at position 94, the variations in human iNKT TCR-α chains occurred most often at position 93 of the CDR3α.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, these TCR-α variations strongly influenced the affinity of human iNKT TCRs for various antigenCD1d complexes, irrespective of the TCR-β chain with which they were paired (39). However, in contrast with our results where variations were most common at position 94, the variations in human iNKT TCR-α chains occurred most often at position 93 of the CDR3α.…”
Section: Discussioncontrasting
confidence: 99%
“…A serine residue is found at position 93 in the majority of human iNKT TCR-αs, whereas in the mouse iNKT TCRs this position is a glycine residue. Although this position 93 does not directly contact CD1d, dynamic modeling studies suggested that it can nonetheless affect the conformation of the CDR3α loop (39). The reason for this difference between species is currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the pivotal role of the V-J transition for iNKT TCR function as has been shown before for position 93 in human [10,11]. In mouse, we could confirm this influence for the naturally occuring G93A substitution, where previously only variations at position 94 had been addressed [16].…”
Section: Discussionsupporting
confidence: 91%
“…Despite demonstration of the pivotal role of invariant CDRαs, the V-J transition, which is the only source of natural variation within the invariant α chain, has been shown to significantly influence the binding to several antigens in humans. Most human iNKT TCRα chains harbor a serine at position 93 that can be replaced either by threonine, asparagine, or isoleucine concomitant with loss of avidity [11], explaining the importance of a canonical iNKT TCRα chains sequence after rearrangement. Several natural variations of position 93 have also been described for the mouse iNKT TCRα chain, where the canonical glycine has been replaced by alanine, isoleucine, or valine [5,6,[12][13][14][15].…”
mentioning
confidence: 99%
See 1 more Smart Citation